Local Government Financial Institutions in Poland and the European Union - Srokosz, Witold; Kopyściański, Tomasz; Kowalczyk, Rafał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The book is the culmination of research conducted as part of a research project financed by the Polish National Science Centre. The first thread of this research concerns the functioning of local government financial institutions in Poland and the European Union. However, the second thread concerns the preparation of basic assumptions for the legal regulation of the system of Polish depository and credit institutions (i.e. credit institutions, according to the European Union nomenclature), which are controlled by Polish local government units. In practice, there are two types of local government financial institutions in the European Union: credit institutions and credit guarantee funds. In Poland, of these two types of local government financial institutions, there are local government guarantee funds and loan funds created by voivodships. However, there are no local government depository and credit institutions on the Polish financial market at all. These findings were reflected in the structure of the monograph. It analyses the existing legal regulations regarding local credit institutions and credit guarantee funds in selected European Union countries, as well as the existing legal regulations in Poland regarding the creation of local government financial institutions by local government units. The economic conditions of functioning of guarantee funds in Poland were also taken into account. Then, the findings were used to prepare a proposal for a general outline of the legal regulation of municipal credit institutions in Poland.The main purpose of the monograph is not so much to give the best recommendation for Polish municipal depository and credit institutions, but rather to provide material for further,intensified discussion on such institutions, or even more broadly – the role, significance and legal regulation of local government financial institutions
Keywords: financial institutions; local government; local government units; local government financial institution; non-banking institution; municipal economy; financial innovation; credit institutions; credit guarantee fund; municipal credit institution; local government credit guarantee institution; savings bank; cooperative bank; local bank; CRD IV; communal savings bank; loan fund; small and medium-sized enterprises; financed SMEs; SMEs; Sparkasse